Magic of high-order van Hove singularity - Noah F. Q. Yuan (Nature Portfolio, 2019)
Correlation effect is essential to stabilize exotic phases such as superconductivity in twisted bilayer graphene. Here, Yuan et al. predict significantly enhanced electron correlation effects due to an emergent high-order van Hove singularity in a two dimensional moiré superlattice.